Behind the "Powderworks": Hannah Josephson and "The Tin Flute." - Whitfield, Agnes (Canadian Literature)
This article explores the nature of nationalistic identity and its effect on international literature translations. The translating errors of Hannah Josephson seen in "The Tin Flute," based on the book "Bonheur d'occasion," by Gabrielle Roy, are analyzed. The author suggests that through translating language, the national ideals and worldviews of the writer and translator come to effect each other and the work.